Detection of newly synthesized RNA reveals transcriptional reprogramming during ZGA and a role of Obox3 in totipotency acquisition - Mizuki Sakamoto; Aoi Ito; Sayaka Wakayama; Hiroyuki Sasaki; Teruhiko Wakayama; Takashi Ishiuchi (Cell Reports, 2024)
Summary: Zygotic genome activation (ZGA) after fertilization enables the maternal-to-zygotic transition. However, the global view of ZGA, particularly at initiation, is incompletely understood. Here, we develop a method to capture and sequence newly synthesized RNA in early mouse embryos, providing a view of transcriptional reprogramming during ZGA. Our data demonstrate that major ZGA gene activation begins earlier than previously thought. Furthermore, we identify a set of genes activated during minor ZGA, the promoters of which show enrichment of the Obox factor motif, and find that Obox3 or Obox5 overexpression in mouse embryonic stem cells activates ZGA genes. Notably, the expression of Obox factors is severely impaired in somatic cell nuclear transfer (SCNT) embryos, and restoration of Obox3 expression corrects the ZGA profile and greatly improves SCNT embryo development. Hence, our study reveals dynamic transcriptional reprogramming during ZGA and underscores the crucial role of Obox3 in facilitating totipotency acquisition.